Arsenite release on enzymic transformation of arsonomethyl substrate analogues: a potentially lethal synthesis by glycerol-3-phosphate dehydrogenase. - Mutenda, E K (1995)
The isosteric arsenical analogue of glycerol 3-phosphate, 3,4-dihydroxybutylarsonic acid, is a good substrate for rabbit muscle glycerol-3-phosphate dehydrogenase. Its oxidation is accompanied by release of arsenite. This release seems to be due to a spontaneous elimination of arsenite by 3-oxoalkylarsonic acids, as it is also observed in (1) the oxidation of 3-hydroxypropylarsonic acid by yeast alcohol dehydrogenase, (2) treatment of 3,4-dihydroxybutylarsonic acid with periodate and (3) nonenzymic transamination of the glutamate analogue 2-amino-4-arsonobutyric acid. Enzymic formation of 3-oxoalkylarsonic acids in cells can therefore be lethal, as arsenite is poisonous to most organisms because of its high affinity for dithiols such as dihydrolipoyl groups.